LITERATUR STUDI MENGENAI ADSORBEN LIMBAH CANGKANG HEWAN LAUT DALAM BERBAGAI KEILMUAN - Haris, Muhammad Naoval; Astryani, Nilam Lingga; Madusari, Benny Diah; Ramadhani, Farchan Mushaf Al (Universitas Majalengka, 2024)
The utilization of marine animal waste as a base material for adsorbents has become an increasingly popular research topic across various scientific fields, including chemistry, environmental science, and materials science. Waste from marine animals, such as crab shells, oyster shell, seashell, and shrimp shell, possesses high potential to be processed into adsorbents due to their abundant calcium carbonate, chitosan, and protein content. The use of this waste as adsorbents not only provides a solution to environmental issues related to the accumulation of organic waste but also offers cheaper and eco-friendly alternative for water treatment, air purification, and contaminated soil remediation. Research has shown that marine animal waste-based adsorbents are effective in removing various pollutants, including heavy metals, textile dyes, and hazardous organic compounds. With specific modification techniques, the performance of these adsorbents can be enhanced, making them competitive with commercial adsorbents. Overall, the use of marine animal waste as adsorbents represents an innovative approach that contributes to waste reduction and the enhancement of environmental sustainability.